Teaching Haiti : Strategies for Creating New Narratives - Orlando, Valerie, 1963-; Accilien, Cecile, 1973- (Book collections on Project MUSE., 2021)
"This volume provides guidance on teaching about Haiti's history and culture from a multidisciplinary perspective, offering ways of reshaping old narratives through women's and gender studies, poetry, theater, art, religion, language, politics, history, and popular culture"--